The Application of Inventory Models to Attain Optimality in a Cement Manufacturing Firm - Adebayo. T ADEDUGBA; Olaleke O OGUNNAIKE; Kingsley A ADEYEMOA; Busola E KEHINDE (Communications of International Proceedings, 2020)
The measure of stock will decide or influence the flow of the manufacturing procedure as well as the adequacy and proficiency of an organization. The cement factory produces more than 8 million packs of cement each day. The accomplishment of the cement factory depends upon the accessibility to crude or raw materials. Along these lines, in the event that the inventory of crude materials can not address the requirement of production, at that point the production procedure will be disruption. On the account of overloading production volume will be excessive. Inventory and production optimality can be achieved by utilizing economic request quantity and production request quality model. These techniques were utilized by the means of QM software, to get an optimal request amount of 15452 and 31866 respectively and the yearly holding cost for inventory or stock is 6,711,223,000 Naira and the yearly holding cost for production is 2,768,032,000 Naira.
Keywords: Optimality; Inventory; Production Request Quantity and Economic Request Quantity.